A novel full-length transcriptome resource from multiple immune-related tissues in turbot (Scophthalmus maximus) using Pacbio SMART sequencing. Issue 129 (October 2022) - Fu, Qiang; Zhang, Pei; Zhao, Shoucong; Li, Yuqing; Li, Xingchun; Cao, Min; Yang, Ning; Li, Chao
Abstract: Turbot ( Scophthalmus maximus ) is an important cold-water economic fish. However, the production and development of turbot industry has been constantly hindered by the frequent occurrence of some diseases. Lacking full-length transcriptome for turbot limits immune gene discoveries and gene structures analysis. Therefore, we generated a full-length transcriptome using mixed immune-related tissues of turbot with PacBio Sequel platform. In this study, a total of 31.7 Gb high quality data were generated with the average subreads length of 2618 bp. According to the presence of 5′ and 3′ primers as well as poly (A) tails, FL (Full-length) and NFL (Non-full-length) isoforms were obtained. Meanwhile, we identified 32, 003 non-redundant transcripts, 76.02% of which was novel isoforms of known genes. In addition, 12, 176 alternative splicing (AS) events, 6614 polyadenylation (APA) events, 1905 transcription factors, and 2703 lncRNAs were identified. This work is a comprehensive report on the full-length transcriptome of immune-related tissues of turbot, and it also provides valuable molecular resources for future research on the adaptation mechanisms and functional genomics of turbot. Highlights: Full-length transcriptome of turbot was generated using SMRT Sequencing technology. The FL transcriptome comprised 32, 003 non-redundant transcripts. 12, 176 AS events, 6614 APA events, 2703 lncRNAs, and 1905 TFs were identified. Novel genes related to immunity from novel genes and unmapped transcripts were identified.